„Inny” jako wytwór imaginacyjnej geografii a globalizacja - Błahut-Prusik, Jadwiga (Studia Europaea Gnesnensia, 2019)
This paper discusses creation of the image of the Other from the standpoint of globalization. The objective is to prove the thesis that due to its particular nature, global reality does not tolerate the dichotomy of us vs. them. Also, it is not invalidated by the awareness that one’s own and the alien are more con-tiguous and permeate one another to a greater extent than ever before. The only elements which do change are the contexts surrounding that distinction and the tools of its production and dissemination. Within the consciousness, in the social notions and structures of knowledge, the post-colonial era remains profoundly colonial.